Conservation breeding of the Northern river terrapin Batagur baska at the Vienna Zoo, Austria, and in Bangladesh. Issue 1 (5th December 2014) - Weissenbacher, A.; Preininger, D.; Ghosh, R.; Morshed, A. G. J.; Praschag, P.
Abstract : Wild populations of the Northern river terrapin Batagur baska have been decimated to such an extent that the species can be considered as ecologically extinct. Harvesting and habitat reduction are the main reasons for the drastic demise of B. baska, which formerly inhabited rivers and estuaries in East India, Bangladesh and Myanmar. A cooperative in situ and ex situ conservation project was established to secure the survival of this large river terrapin. In 2010, at Vienna Zoo, Austria, the first two captive‐bred juveniles of the project hatched and presented an opportunity to call attention to this Critically Endangered species. With combined efforts a breeding population has been assembled in Bangladesh's Bhawal National Park and 84 juveniles have been reared in the past 2 years. Project‐Batagur demonstrates how zoos can play a key role in sustainable long‐term conservation of threatened species.